Rare bacterial subcommunity drives nutrient cycling in phyllosphere habitat of evergreen conifers - Bing Li; Mingyang Fu; Guangze Jin; Zhili Liu (Microbiology Spectrum)
ABSTRACT Phyllosphere bacteria are crucial for pathogen resistance, stress tolerance, and productivity maintenance of host plants and further have potential effects on ecosystem functions. However, whether and how assembly patterns of both abundant and rare subcommunities changed across needle age cohorts, and their relative contributions to nutrient cycling in phyllosphere habitat of evergreen conifers are still unclear. Here, we examined both phyllosphere abundant and rare bacterial subcommunities in three needle age cohorts of the representative evergreen conifers in mixed broadleaved-Korean pine forests throughout Northeast China. We found that dispersal limitation and ecological drift dominated abundant and rare subcommunities, respectively. Deterministic assembly gradually increased with needle aging, which was mainly attributed to the increased needle chemical defense traits such as flavonoids. We further showed that multiple nutrient cycling in phyllosphere habitat was regulated by the rare subcommunity, closely related to the variations in diversity and composition. Collectively, our findings facilitate us in clarifying the mechanisms underlying the formation and succession of phyllosphere bacterial subcommunities across needle age cohorts and emphasize the vital role of rare subcommunities in promoting ecosystem functions.IMPORTANCEHost-associated microbial communities are critical for host health. However, the relative importance of abundant and rare subcommunities in driving nutrient cycling in phyllosphere habitat across needle age cohorts of evergreen conifers remains unknown. Here, we showed the different assembly mechanisms of abundant and rare subcommunities and emphasized the ecological role of rare subcommunities in promoting ecosystem functions. This is useful for understanding the formation and succession dynamics of plant microbiome to advance future applications with microbial agents to sustainable productivity and reduce diseases.